2020
DOI: 10.1021/acsami.0c04934
|View full text |Cite
|
Sign up to set email alerts
|

UV-Stable and Highly Efficient Perovskite Solar Cells by Employing Wide Band gap NaTaO3 as an Electron-Transporting Layer

Abstract: Organic–inorganic halide perovskite solar cells (PSCs) still suffer from stability issues which are caused by possible erosions from moisture, ultraviolet (UV) light, heat, and so forth. An electron-transporting layer (ETL), that is, TiO2, is a key component for state-of-the-art PSCs. However, UV-caused desorption of O2– in TiO2 would accelerate the degradation of PSCs. Herein, we explored perovskite oxide, NaTaO3, for the first time as an alternative ETL in PSCs. NaTaO3 as an ETL can effectively avoid the dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Moreover, the higher the energy of incident UV radiation, the greater is the degradation . Thus, the current understanding of UV stability of PSCs proposes that, if UV radiation is blocked effectively, the PSCs should become photostable. , However, this is often not encountered in practice, as demonstrated by exposing unencapsulated PSCs to radiation of a UV-free white light-emitting diode (LED) at 20 °C in an inert atmosphere for 250 h where a loss of more than 20% in efficiency is observed . This observed instability of PSCs toward UV-filtered light suggests that other parts of the solar spectrum could also be contributing to the photo-degradation of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the higher the energy of incident UV radiation, the greater is the degradation . Thus, the current understanding of UV stability of PSCs proposes that, if UV radiation is blocked effectively, the PSCs should become photostable. , However, this is often not encountered in practice, as demonstrated by exposing unencapsulated PSCs to radiation of a UV-free white light-emitting diode (LED) at 20 °C in an inert atmosphere for 250 h where a loss of more than 20% in efficiency is observed . This observed instability of PSCs toward UV-filtered light suggests that other parts of the solar spectrum could also be contributing to the photo-degradation of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Ye et al suggested an improvement in the efficiency of PSCs with NaTaO 3 through thickness control of the NaTaO 3 layer and in combination with a thin modified layer of phenyl-C61-butyric acid methyl ester between the perovskite and the NaTaO 3 layer. [39] Here however, we want to take advantage of the chemical tunability of NaTaO 3 , and by targeted choice of their constituent elements, vary shape and surface composition and test their corresponding device performance. As illustrated in Figure 4b the NaTaO 3 samples are slightly lower than that of FAPbI 3 (−3.79 eV), and their VBMs are significantly lower than that of FAPbI 3 (−5.38 eV).…”
Section: Resultsmentioning
confidence: 99%
“…[ 35–38 ] Recently, solution‐processed NaTaO 3 nanoparticles as an electron transport layer (ETL) have been reported in PSCs. [ 39 ] Ye et al. suggested an improvement in the efficiency of PSCs with NaTaO 3 through thickness control of the NaTaO 3 layer and in combination with a thin modified layer of phenyl‐C61‐butyric acid methyl ester between the perovskite and the NaTaO 3 layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the common ternary semiconductor oxides mentioned earlier, SrSnO 3 , [ 156 ] BaTiO 3 , [ 157 ] NaTaO 3 , [ 158 ] and Ti 0.5 Fe 0.5 O x [ 159 ] have also been reported in PSCs. In summary, ternary semiconductor oxides seem to induce faster crystallization, high transparency, and better surface coverage for perovskite layers.…”
Section: Preparation and Characteristics Of Electron Transport Materialsmentioning
confidence: 99%